Maya Narrative Arts - Bassie-Sweet, Karen, 1952-; Hopkins, Nicholas A. (Book collections on Project MUSE., 2018)
"A comprehensive and innovative analysis of the principles of Classic Maya narrative arts and applying those principles to major Palenque monuments. Demonstrating recent methodological shifts in the examination of art and inscriptions away from technical issues and toward the poetics and narratives of texts including relationships between images"--Provided by publisher